A Numerical Study About the Flow Around Motorbike with Different Types of Fairing When Travel Through Crosswind - Abdul Razak, Muhammad Alief Firzhan; Hassan, Nurhafizzah; Ishak, Izuan Amin (Journal of Automotive Powertrain and Transportation Technology, 2023)
Riding a motorbike possess to a dangerous situation because of its stability and balance. Crosswind has a significant impact on riding since, with a strong gust, it can easily drive the motorbike off the road or into another lane or traffic. A numerical study has been conducted to investigate the aerodynamic loads of the drag, side, and lift coefficient and to analyze the flow pattern occurs of the motorbike with different types of fairing when travel under various angle of crosswind that was set ranging 0?, 15?, 30?, 60? to 90?. Two models of Yamaha YZF M1 with different types of fairing were designed using SolidWorks 2020 and then simulated using Ansys CFX with 25m/s as the velocity for main and crosswind inlet. The aerodynamic loads coefficient was calculated for each model and the streamlines flow were analyzed. The aerodynamic loads coefficient was found increases as the yaw angle increases. Half fairing model was found to have higher aerodynamic coefficient compared to fully fairing model since half fairing model was not aerodynamic shape.